Citizens' expectations about social protection in multilevel governance: The interplay between national and supranational institutions. (23rd December 2021) - Baute, Sharon
Abstract: Two contrasting perspectives can be identified in the current literature on the relationship between European integration and the welfare state. On the one hand, the race to the bottom thesis presumes that welfare spending will be reduced to the lowest common denominator. On the other hand, the upward convergence thesis suggests that European integration supports and strengthens the capacities of national welfare states. This suggests that the consequences of European integration for national social protection systems are ambiguous. The current study contributes to this debate, by investigating the relationship between European integration and the welfare state from the perspective of public opinion. Do European citizens envision a race to the bottom or an upward convergence in social protection, and why so? Analysing data from the European Social Survey in 18 EU countries, the article reveals that the material benefits brought by national and supranational institutions, jointly shape citizens' expectations about the EU–welfare nexus, although in opposite directions. Generous national welfare provision fuels expectations that European integration fosters a race to the bottom for social protection levels, while higher receipts from EU Structural Fund programs and individual trust in EU institutions raise expectations of the EU as a catalyst of upward convergence in social standards. The implications of these findings for social policymaking in multilevel governance regimes are discussed.